Efficient Path Planning Based On Hybrid Routing Protocols over A Vanet - Prabha, S. Santhana (IJRDO -Journal of Computer Science Engineering, 2017)
Vehicular Ad-hoc Network (VANET) is an emerging communication Infrastructure which facilitates the connectivity among vehicles through vehicle-to- vehicle (v2v) and vehicle-to-roadside (v2R) communications and is characterized by high dynamic topology of nodes in the network. Due to this high mobility of vehicles it is quite challenging to perform packet delivery from source to destination in case of any destruction or congestion in the network. In order to overcome this problem a novel path planning technique must be implemented reducing packet loss and end to end delay which includes communication among vehicles, road side units(RSUs) and vehicle traffic servers. Hence we propose a routing protocol with GPS and map aware capabilities that includes four metrics such as distance to destination, vehicle’s density, vehicle’s trajectory and available bandwidth in order to make forwarding decisions. This protocol is being justified and it is shown that it reduces packet loss and end to end delay in the network thus increasing the efficiency of routing.